Comparison of effects of two kinds of fluid for resuscitation on bacterial translocation and inflammation of small intestine in rats with hemorrhagic shock - Gao, Xin-yue (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2006)
OBJECTIVE: To investigate the effects of Ringer's solution (RS) or 6% hydroxyethyl saline (HES) on bacterial translocation and inflammation of the small intestine in rats with hemorrhagic shock